TEACHING VOCABULARY TO CHILDREN THROUGH KINESTHETIC ACTIVITIES - Abdalyazova , Yulduz Kahramon qizi (INTERNATIONAL CONFERENCES, 2023)
In order to develop teaching foreign language in classroom, previous researches demonstrated how learning styles have influenced the effectiveness of teaching students. Also, this study aims to add a positive change in classroom teaching with versatile useful activities. The information portrays that the majority of the children are kinesthetic learners. It is suggested that in order to enhance learning vocabulary and encouraging children to be active in class, their learning styles must be taken into consideration.